Immunotactoid Glomerulopathy and Cryoglobulinemic Nephropathy: Two Entities with Many Similarities. A Unified Conceptual Approach*. (August 2015) - Herrera, Guillermo A.; Ojemakinde, Kunle O.; Turbat-Herrera, Elba A.; Gu, Xin; Zeng, Xu; Iskandar, Samy S.
Abstract Immunotactoid glomerulopathy is a rare disorder that has been characterized at the ultrastructural level. Due to its rarity, there are few comprehensive studies relating to this disorder. Electron microscopy essentially characterizes this disease. The glomerular electron dense deposits which are typical of this condition consist of aggregates of highly organized microtubular structures of various diameters, but generally measuring 30–50 nm in width with a propensity to dispose themselves in parallel bundles intersecting in different planes. This study compares a large series of patients with cryoglobulinemic nephropathy with a series of patients with immunotactoid glomerulopathy to address whether there may be similarities that warrant considering these two entities part of a spectrum. This study reviews the clinicopathologic features of both entities and emphasizes ultrastructural findings that characterize them. Significant immunomorphologic overlap was found when these two disorders were compared in this study. There were also striking similarities in clinical presentation/behavior, laboratory findings and prognosis. Proteomic analysis has also demonstrated similar spectra for both entities. We postulate that immunotactoid glomerulopathy and cryoglobulinemic nephropathy are part of the spectrum of renal manifestations in patients with circulating cryoglobulins and renal disease.